Role of Medicinal Plants in Health Care and Rural Economy in the Tribals of Satpura Plateau Region of Central India - Pandey, A. K.; Shukla, P. K. (Indian Forester, 2008)
The Satpura plateau region of Central India is home of numerous herb species. The agroclimatic conditions prevailing in the region provides an ideal habitat for the natural growth of variety of plants and herbs, which provide raw materials for pharmaceutical, phytochemical, food, flavoring and cosmetic industries. The paper provides information on 92 medicinal plants used by the Gond, Bharia and Korku tribes of Chhindwara, Betul, Hosangabad and Seoni district of Madhya Pradesh, India, for the treatment of various diseases. Traditional medicine remains an integral part of the health system in this region of Central India. Medicinal plants of forest origin hold great promise to enhance the health and source of livelihood to the forest dwellers.